Synchrony of Respiratory Sinus Arrhythmia in Parents and Children with Autism Spectrum Disorder: Moderation by Interaction Quality and Child Behavior Problems. Issue 3 (1st October 2020) - Wang, Hui; Suveg, Cynthia; West, Kara B.; Han, Zhuo R.; Zhang, Xutong; Hu, Xiaoyi; Yi, Li
Abstract : Parent–child physiological synchrony, the matching of physiological states between parents and children, is theorized to be important for typically developing (TD) children, but less is known about this process in families of children with autism spectrum disorder (ASD). In a sample of 29 children ( M age = 8.00 years, SD = 1.51 years) with ASD and 39 TD‐matched children ( M age = 7.32 years, SD = 1.36 years) and their primary caregivers ( n = 68), we examined whether parent–child dyads showed physiological synchrony indexed by respiratory sinus arrhythmia (RSA) during an interaction, and whether RSA synchrony differed by parent–child interaction quality and child behavior problems. Results indicated that dyads with TD children showed stronger positive RSA synchrony than dyads with children with ASD. Furthermore, for families of children with ASD, RSA synchrony was stronger in families with higher interaction quality and fewer child internalizing problems. These results provide preliminary evidence of parent–child RSA synchrony in families of children with ASD and identify factors that may influence this physiological process. Implications of these findings for social and emotional development in children with ASD are discussed. Lay Summary: Parents and children can get "in tune" with one another at the biological level – a process called physiological synchrony. We studied physiological synchrony in families of children with autism spectrum disorder (ASD) in comparison to same‐aged children who had no mental health disorders. We also examined how physiological synchrony might be associated with parent–child interaction quality and child behavior problems. We found that families with a child with ASD showed weaker physiological synchrony than families with a child who was typically developing. Further, we found that physiological synchrony was stronger when parents and children with ASD showed higher interaction quality and when children with ASD had lower internalizing problems. These findings contribute to our understanding of family functioning in the context of ASD and have potential implications for future work.